The Role of Notaries and PPAT in Protecting Gayo Customary Rights - Aminsyah Aminsyah; Andri Winjaya Laksana (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
Ulayat rights are the rights of indigenous peoples over all agrarian resources that exist within the territory of the indigenous peoples concerned. Thus the object of customary rights includes all agrarian resources (earth, water and natural resources contained therein). This writing aims to analyze the legal position of the customary rights of the Gayo people in Gayo Lues Regency and the role of Notaries and PPAT in protecting the customary rights of the Gayo people in Gayo Lues Regency. This writing is analyzed qualitatively by using the analysis knife of Islamic justice theory, legal certainty theory, and inheritance division theory. The results of the study indicate that the position and position of the customary rights of the customary law community in the National Land Law is very important, the hierarchy is higher than the individual/individual rights to land. Customary law communities live and develop in accordance with the order of values and norms that they believe and obey as truth, including in this case customary norms in the concept of land tenure. Article 3 of the UUPA states that the acknowledgment of the existence of Ulayat rights of the customary law community as long as in reality it still exists, meaning that if in fact it does not exist, then the Ulayat rights can no longer be recognized, cannot be revived and new Ulayat rights cannot be created. The regulation of Ulayat rights is left to the Customary Law community. In providing services to the community, a Notary/PPAT has the duty to serve applications to make certain land deeds referred to in the regulations regarding land registration and the PPAT Position regulations.